The Cranial Analysis of Eight Skulls from Collective Grave of the Early Bronze Age Vučedol Site (East Slavonia, Croatia) - Hincak, Zdravka (Array, 2013)
The collective grave of the Vučedol culture signed as „grave 3/1985“ with skeletons of eight persons, represents the most important burial of this culture on the eponimic site in East Croatia, with several indications of human sacrifice. Anthropological and radiological analysis were performed on crania remains of the individuals, specifically on the skulls of one male and seven females. Nondestructive methods embraced craniometrical analysis, analysis of cranial non- metric traits and multivariate distance analysis, with a help of radiological methods, to detect every distinct anatomical characteristic of the skulls. All methods used in this work tried to present similarities and a possible homogeneity of the analysed individuals.